2022
DOI: 10.1007/s11252-022-01302-y
|View full text |Cite
|
Sign up to set email alerts
|

Phenology of grassland plants responds to urbanization

Abstract: Understanding phenological responses of plants to changing temperatures is important because of multiple associated ecological consequences. Cities with their urban heat island can be used as laboratories to study phenological adaptation to climate change. However, previous phenology studies focused on trees and did not disentangle the role of micro-climate and urban structures.We studied reproductive phenology of dry grassland species in response to micro-climate and urbanization in Berlin, Germany. Phenologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…2), on the other hand, as tentative evidence for adaptation. Previous studies have demonstrated shifts in flowering phenology for the overall urban plant community in relation to the UHIE [44][45][46] but have always relied on field observations in whole ecosystems. Such observations cannot distinguish between phenotypic plasticity and genetic divergence.…”
Section: Discussionmentioning
confidence: 99%
“…2), on the other hand, as tentative evidence for adaptation. Previous studies have demonstrated shifts in flowering phenology for the overall urban plant community in relation to the UHIE [44][45][46] but have always relied on field observations in whole ecosystems. Such observations cannot distinguish between phenotypic plasticity and genetic divergence.…”
Section: Discussionmentioning
confidence: 99%
“…The dispersion in the plant assemblages between sites was much wider in the students' vegetation collections compared with the expert's. A difference in the species composition between the sites could be expected, for example, to be affected by the different degrees of urbanization per sample location [73,74] or correlations between phenology and microclimatic conditions [75]. However, these factors applied to all groups and could not account for the large difference in dispersion between student and expert surveys, because species composition would not change that dramatically from 2020 to 2021.…”
Section: Discussionmentioning
confidence: 99%